Penulisan Fiksi Sebagai Wahana Artikulasi Gagasan Generasi Muda - Agusniar Rizka Luthfia; Eka Nada Shofa Alkhajar; Sonhaji Sonhaji; Desiderius Priyo Sudiyo (LPPM Universitas Timor, 2019)
Adolescence is known as a critical and dynamic period. At this period, adolescents also have abundant energy. This energy certainly needs to be channeled to the right way or otherwise it potentially turned into the wrong way. The community devotion in the form of fiction writing training is one of the ways to channel the adolescent energy. It carried out with lectures, discussions, accompaniments and practices methods. The target of community devotion joined the training with great enthusiasm. The result achieved from this community devotion is that the target of community devotion became able to write uptheir ideas and creativities in the form of fiction.